Thomas D. Davis, The Code of the City of Lynchburg, Va., Containing the Charter of 1880, with the Amendments of 1884, 1886 and 1887, and the General Ordinances in Force July 1st, 1887, Also a Digest of Acts of Assembly and of Ordinances Affecting the Rights and Interests of the City of Lynchburg and its Citizens, Together with a Brief Sketch, Historical and Statistical, at 116, ch. 19, § 14 (1887) - (:unkn) unknown (General Publisher, 1887)
No person shall set off any fireworks or explode any popcrackers within the city limits. No person shall discharge any gun, pistol or other fire-arm within the city limits. No person shall, without the written consent of the Mayor, fire a cannon in the city, nor shall any cannon be fired within one hundred yards of any dwelling-house without the consent of the owner or occupant of such house. For violations of this section, the penalty shall be not less than one dollar nor more than ten dollars for each offence.
--
Keywords: DISCHARGE